Methods, Standards and Components for Wireless Communications and Power Transfer Aimed at Intra-Vehicular Applications of Launchers - Francesco Fusco; Vittorio Ugo Castrillo; Hernan Maximiliano Roque Giannetta; Marta Albano; Enrico Cavallini (Aerospace, 2024)
In the world of space systems and launchers in particular, there is always a strong demand for the reduction of the weight of all components/subsystems that are not related to the payload and simplification of the integration phase. A possible solution to both these problems is the replacement of cables and connectors with wireless systems for communication and power supply. With this aim, a survey was carried out through an analysis of the technical/scientific literature available on wireless communication standards and electric power transfer methods. To evaluate wireless systems’ effective applicability, the existence of applicable standards and commercial components that could facilitate their implementation was also verified. To provide information on specific applications, a synthesis of experiences in the aeronautical and space fields of wireless system demonstrators was reported. Consequently, it is clear that there is interest in the subject, but some applications are still limited to the demonstration of systems or, at most, to non-critical functions. Since wireless power transfer methods need less energy from the sensor nodes, a brief investigation into the architectures and components necessary to implement low-power sensor nodes is also included in this study.